SOCIAL PSYCHOLOGICAL FACTORS AFFECTING MENTAL DISORDERS OF NATIONAL GUARD MILITARY PERSONNEL - Rahimov O'tam Alikhojaevich (American Journals, 2022)
In this article, opinions were expressed about the social psychological factors affecting the mental disorders of the National Guard military personnel.
Keywords: military, national guard, agility, perception, coordination, sensory organs.